El llanito - Canseco Quiroz, Elba Berenice; Aguirre, Mara; Cebada Orozco, María Guadalupe; Ortiz Chao, Claudia Gabriela; Vazquez Lemus, Andrea (Concurso de estudiantes 2021 Infonavit, 2021)
El proyecto urbano arquitectónico en el conjunto habitacional